Bandung Creative Class: Fostering Creative Characters of Citizens in Bandung City as a Strengthening of 21st Century Competency - Agus Rendra; Rahmat Rahmat (Journal of International Conference Proceedings (JICP), 2020)
The insistence of challenges from digitalization and transformation of the 4.0 era made the government and the people of Bandung as a creative city of UNESCO must improve 21st century competencies, one of which was creative. This study aims to analyze the development of creative character by the Bandung City Government in developing competent citizens of the 21st century. With the case study method, this research involves three research subjects which include the city government, community, and residents who are fostered. The results showed that the coaching process had a top down and bottom up direction. Coaching is carried out through policy and non-policy competency development programs from the government and community collaborative forums. The process includes the analysis of program plans, program implementation, evaluation of results.